Assessing joint toxicity of chemicals in Enchytraeus albidus (Enchytraeidae) and Porcellionides pruinosus (Isopoda) using avoidance behaviour as an endpoint - Loureiro, Susana
Contamination problems are often characterized by complex mixtures of chemicals. There are two conceptual models usually used to evaluate patterns of mixture toxicity: Concentration Addition (CA) and Independent Action (IA). Deviations from these models as synergism, antagonism and dose dependency also occur. In the present study, single and mixture toxicity of atrazine, dimethoate, lindane, zinc and cadmium were tested in Porcellionides pruinosus and Enchytraeus albidus, using avoidance as test parameter. For both species patterns of antagonism were found when exposed to dimethoate and atrazine, synergism for lindane and dimethoate exposures (with the exception of lower doses in the isopod case study) and concentration addition for cadmium and zinc occurred, while the exposure to cadmium and dimethoate showed dissimilar patterns. This study highlights the importance of dose dependencies when testing chemical mixtures and that avoidance tests can also be used to asses the effects of mixture toxicity. (C) 2008 Elsevier Ltd. All rights reserved.